Approximate Controllability of Sobolev-Type Fractional Neutral Evolution Inclusions - Tamilselvan, M.; Murugesu, R. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, we establish a set of sufficient conditions for the approximate controllability for a class of Sobolev-type fractional neutral evolution inclusions in Banach spaces. We use Bohnenblust-Karlin’s fixed point theorem to prove our main results. Further, we extend our result to study the approximate controllability for nonlinear fractional control system with nonlocal conditions. An example is also given to illustrate our main results.